Inflammation in Fabry disease: stages, molecular pathways, and therapeutic implications - Kurdi, Hibba; Lavalle, Lucia; Moon, James C. C.; Hughes, Derralynn (Frontiers in Cardiovascular Medicine, 2024)
Fabry disease, a multisystem X-linked disorder caused by mutations in the alpha-galactosidase gene. This leads to the accumulation of globotriaosylceramide (Gb3) and globotriaosylsphingosine (Lyso-Gb3), culminating in various clinical signs and symptoms that significantly impact quality of life. Although treatments such as enzyme replacement, oral chaperone, and emerging therapies like gene therapy exist; delayed diagnosis often curtails their effectiveness. Our review highlights the importance of delineating the stages of inflammation in Fabry disease to enhance the timing and efficacy of diagnosis and interventions, particularly before the progression to fibrosis, where treatment options are less effective. Inflammation is emerging as an important aspect of the pathogenesis of Fabry disease. This is thought to be predominantly mediated by the innate immune response, with growing evidence pointing towards the potential involvement of adaptive immune mechanisms that remain poorly understood. Highlighted by the fact that Fabry disease shares immune profiles with systemic autoinflammatory diseases, blurring the distinctions between these disorders and highlighting the need for a nuanced understanding of immune dynamics. This insight is crucial for developing targeted therapies and improving the administration of current treatments like enzyme replacement. Moreover, our review discusses the complex interplay between these inflammatory processes and current treatments, such as the challenges posed by anti-drug antibodies. These antibodies can attenuate the effectiveness of therapies, necessitating more refined approaches to mitigate their impact. By advancing our understanding of the molecular changes, inflammatory mediators and causative factors that drive inflammation in Fabry disease, we aim to clarify their role in the disease's progression. This improved understanding will help us see how these processes fit into the current landscape of Fabry disease. Additionally, it will guide the development of more effective diagnostic and therapeutic approaches, ultimately improving patient care.